Use of Solar Energy in Removal of Quinaldine Red from Effluents Using PbS as Semiconductor - YADAV, INDERJEET; BHARDWAJ, SHIPRA (Asian Journal of Chemistry, 2010)
Quinaldine red was removed in presence of sunlight from industrial effluents using Pbs as semiconductor. The reaction was found to follow pseudo first order rate law. Effect of variation of factors like pH, concentration of dye, amount of semiconductor, intensity of light, etc. were studied and a tentative mechanism is also proposed.